Moral and religious paranoia in the literature of Caliber and Algarve: The Abbasid period is a model - كامل إسراء طارق (Al-Adab Journal, 2019)
Our Arab literary heritage is attractive and Hausa Linfak tempts scholars and researchers in ancient and recent research into its hidden places and worlds, which in quite a few of them involve the paradoxes and antagonisms of this heritage in its various literary genres, which were incorporated under the poetry and prose . Perhaps we are wrong if we say that the preoccupation of most literary and monetary studies, especially the old ones research and extrapolation of literary productions central or official that we may express such as those that investigate the literary and monetary phenomena in this poet or that or that community of poets and other traditional topics that worked These scholars are searching for a lot of literary and intellectual currents that do not complement our Arab heritage without looking at their sources and even trying to eliminate them in some cases, despite the fact that they included creative means that contributed to enriching our literary and monetary heritage in a different way. Day’s through . The phenomenon of the spread of caliber and al-Shatter as an outlaw and state authority was one of the most prominent phenomena that occupied our ancient Arab societies, especially the Abbasid society, which caused the neglect of power by its impoverished and poor groups in their behavior. The political activity of this social group was accompanied by a wide variety of literary activities, which included many paradoxes and contradictions, including the religious and moral paradox, which we have noticed in their heroic and folkloric stories and stories, as well as their poems which revealed in many of them the emotional side of this group, Religious and moral, who have defended their existence and even rooted in their behavior and if they are moving within the framework of robbery and raid on the rich and the wealthy and influential people specifically, being one of the most important factors marginalization and exclusion Despite the fact that the purpose is not to justify the means, the literary reality of the caliphs and al-Shatter clearly refers to a social and religious role to be played by heroes who belong to the path and stories of this popular trend. They influenced the society positively by establishing the religious and moral grounds in their hearts; the negative is a paradox in the reader’s mind about how these two extremes combine the belief in religion and morals on the one hand and the behavior that negates this belief on the other. This is what we tried to exaggerate in his clergy and to prove or deny this kind of irony in the literature of calves and fables .